Prevalence of metabolic syndrome in Brazilian adults in the last 10 years: a systematic review and meta-analysis - Letícia Teixeira de Siqueira Valadares; Luiza Siqueira Barreto de Souza; Valdir Alves Salgado Júnior; Larissa de Freitas Bonomo; Leandro Roberto de Macedo; Maísa Silva (BMC, 2022)
Abstract Background A cluster of interconnected cardiometabolic risk factors characterizes metabolic Syndrome (MS). The prevalence of MS is increasing worldwide, but there is not a meta-analysis of this prevalence in the Brazilian population. We aimed to determine the prevalence of metabolic syndrome among adult general population in Brazil through a meta‑analysis study. Methods Original research studies were searched at PubMed, Scopus, Web of Science, and SciELO databases, from 2011 to 2021. We used the Joanna Briggs Institute tool to assess the quality of included studies. The random effect model was used to estimate the pooled prevalence of MS. Subgroup and meta-regression analysis were conducted for explored heterogeneity and used the Funnel Plot and Egger's test to assess publication bias. The study was performed based on the criteria of Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Results The search in electronic databases identified 1598 records. From this total, 26 studies were eligible to be included in the final analysis. The overall pooled prevalence among the general population of Brazil was 33% with high heterogeneity observed. By gender, the prevalences were 26% in males and 38% in females. By criteria that was used to define MS, the prevalence were 31% in NCEP ATP III, 25% in JIS, 37% in IDF/NHLBI/AHA/WHF/IAS/IASO and 33% in IDF criteria. The prevalence in different habitat was 34% in urban, 15% in rural, 28% in quilombola and 37% in indigenous. In different regions was 37% in the South, 30% in Southeast, 38% in North, 31% in Northeast and 39% in Midwest. The pooled prevalence of MS with age was < 45 years: 43% and ≥ 45 years: 42% and the prevalence based on year of study implementation was 31% in 2015-2019, 35% in 2010-2014 and 28% in 2005-2009. There were no statistically significant differences between subgroups. Most of the studies showed high quality assessment criteria's except adequate sample size criteria and many studies participants were not sampled in an appropriate way. Conclusions Our review indicates a high prevalence of MS in the healthy Brazilian adult population, when compared to others countries and with a world estimate.